Money Laundering: How It Works and Legal Instruments, A Review Book "Hukum Money Laundering dalam Dimensi Kepatuhan", Dr. Go Lisanawati, S.H., M.Hum & Njoto Benarkah, S.T., M.Sc., Setara Press Malang, 2018, x+84 pages, ISBN: 978-602-6344-54-0 - Aditya, Andra Maula (JILS (Journal of Indonesian Legal Studies), 2021)
This book contains practical knowledge about anti-money laundering in Indonesia and the global context. This book, in addition to presenting various theories regarding the crime of money laundering, also presents various cases and their analysis to provide a comprehensive understanding.